Excitation of Rydberg wave packets with chirped laser pulses - Preclíková, J. (2012)
We study Rydberg wave packets produced by pairs of time separated femtosecond laser pulses. The time separation ranges from femtosecond to picosecond time scales. The wave packets consist predominantly of f states of principal quantum numbers n = 22-32 in Li. With a direct analysis of the field ionization spectra the n-level-resolved classical orbit times are displayed. By chirping the second excitation pulse we demonstrate controlled amplitude oscillations of n-level amplitudes on femtosecond time scales.